2018
DOI: 10.12741/ebrasilis.v11i2.786
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e caracterização de galhas entomógenas em um fragmento florestal em estágio de sucessão ecológica na Amazônia

Abstract: Resumo. O estudo objetivou registrar e caracterizar as galhas entomógenas em duas áreas de floresta em sucessão ecológica em Santarém-PA, de setembro de 2014 a fevereiro de 2015: Campus Tapajós e Bosque Mekdece. Foram coletadas 405 galhas distribuídas em nove morfotipos, os quais estavam associados a 21 espécies de plantas hospedeiras distribuídas em 11 famílias. As plantas hospedeiras que apresentaram maior riqueza de galhas foram Fabaceae com oito morfotipos, Myrtaceae com quatro, seguida de Anacardiaceae e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…More recently, five inventories, with host plants identification and gall characterization, have been published for areas of Amazon rainforest by Araújo et al (2012), Almada & Fernandes (2011), Maia (2011), Silva et al (2011), and Carvalho & Mota (2018 in Pará and Amazonas states. These authors found 112, 309, 77, 27 and 27 morphotypes, respectively, but none of them applied the survey methodology used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, five inventories, with host plants identification and gall characterization, have been published for areas of Amazon rainforest by Araújo et al (2012), Almada & Fernandes (2011), Maia (2011), Silva et al (2011), and Carvalho & Mota (2018 in Pará and Amazonas states. These authors found 112, 309, 77, 27 and 27 morphotypes, respectively, but none of them applied the survey methodology used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Comments: First record of Protium unifoliolatum hosting insect galls in Amazon rainforest areas. However, Protium species were previously recorded hosting insect galls in Amazon rainforest areas by , Araújo & Espírito-Santo Filho (2012), Carvalho & Mota (2018), Maia (2011) and Silva et al (2011.…”
Section: Burseraceae (N= 1)mentioning
confidence: 95%
See 2 more Smart Citations
“…Data on the arthropod fauna associated with insect galls have been reported by several inventories in five phytogeographic domains in Brazil: (1) Amazon Forest (Maia, 2011;Carvalho and Motta, 2018), (2) Atlantic Forest (Maia, 2001(Maia, , 2013(Maia, , 2014Maia et al, 2008Maia et al, , 2014Bregonci et al, 2010;Rodrigues et al, 2014;Maia and Souza, 2013;Carvalho-Fernandes et al, 2016;Maia and Carvalho-Fernandes, 2016;Maia and Mascarenhas, 2017;Ribeiro et al, 2019), and ( 5) Pantanal (Ascendino and Maia, 2018). Several gall inventories of Atlantic Forest areas were carried out in restingas, mainly in the state of Rio de Janeiro (Maia, 2001;Rodrigues et al, 2014;Carvalho-Fernandes et al, 2016), but also in Espírito Santo (Bregonci et al, 2010), and São Paulo (Maia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%